EVALUASI PENERAPAN 5R (RINGKAS, RAPI, RESIK, RAWAT, RAJIN TERHADAP KESELAMATAN KERJA DI PT XYZ. - Dhiya An'nafi; Erdi Suroso; Wisnu Satyajaya; Muhammad Nur (Jurnal Agroindustri Berkelanjutan, 2026)
This study was motivated by the inconsistent implementation of the 5R culture in the workshop area of PT XYZ, which has the potential to reduce productivity and increase the risk of workplace accidents. This study aims to evaluate the implementation of the 5R and analyze its impact on workplace safety as a basis for formulating improvement recommendations. The method used is a mixed-methods approach with a cross-sectional design. Quantitative data were obtained through checklists, while qualitative data were collected through observation, interviews, and documentation. The sample was selected using purposive sampling, involving workers, managers, and OSH academics. Analysis was conducted using gap analysis to compare actual conditions with ideal conditions. The results showed that the implementation of the 5R principles was not yet optimal, with an average achievement of 65.45% (categorized as needing improvement). The “Diligence” component had the highest score (100%), while “Simplicity” had the lowest (25%). A gap of 34.55% was identified, primarily in the aspects of simplicity, neatness, and safety. Therefore, strengthening procedures, supervision, visual controls, and the integration of the 5R principles into the performance system is necessary to improve workplace safety and efficiency.